Kazakh-Polish Literary Relations: A Study of Mutual Influence And Cultural Exchange - Timurovna, Adibaeva Sholpan; Akmaral, Saganayeva; Gulzira, Kuatova; Marina, Asylbekova; Aliya, Ongarbaeva (Journal of Ecohumanism, 2025)
Kazakh-Polish literary relations are a unique phenomenon formed due to historical, cultural and social interactions between the two countries. This article analyzes the main stages of these relations, starting from the period of Polish emigration to Kazakhstan in the 19th century and ending with modern forms of cooperation. The study includes an analysis of translations, joint literary projects and themes touched upon in the works of authors from both countries. Particular attention is paid to the role of translation as a mediator of cultural dialogue, as well as the influence of historical events on literary narratives. The work is based on textual analysis, comparative methodology and archival data. The conclusions of the article emphasize the importance of such relations for strengthening mutual understanding and cultural exchange.